The Absence of Self: An Existential Phenomenological View of The Anatman Experience - Rudolph Bauer (Journal of Philosophical Investigations, 2019)
This paper focuses on the Anatman experience as described by Guatma(6th century BCE). Many Buddhist philosophers consider the absence of self as a foundational experience of Buddhism. This paper elaborates the Buddhist Absence of Self from the View of Existential Phenomenology. The paper articulates the phenomenological difference between the Ontic-Ontological absence of Self in early Buddhism and the Ontic-Ontological presence of Self in Contemporary Existential Phenomenology. Throughout the paper there is an Existential Phenomenological focus on the intertwining of our Sense of Self and our Sense of Being. The sense of self in early Buddhism is being-less, baseless and empty. Empty of What? Empty of Being! There is no presence of Being and no Being of presence. There is no experience of Being. There is no source of Being. There is no source of Being for our mind. The mind is absent of Being. There is no source of Being for us as person. In early Buddhism the absence of self is the absence of Being-ness.